From Legacy to Luminance: Unveiling Fenjius International Ascent in the Baijiu Industry - Geethanjali, Shilpa; Pasha, Mansoor (Journal of Global Economy, Business and Finance, 2025)
This article delves into the contrasting trajectories of Fenjiu and Moutai, two prominent brands in the Chinese Baijiu industry, to explore the factors behind Fenjius remarkable international rise. With a focus on historical legacy, market performance, internationalization strategies, and brand positioning, this academic analysis sheds light on how these brands exemplify the evolving dynamics of the Baijiu sector. By highlighting Fenjius meteoric ascent and its blend of quality, cultural promotion, and adaptability, the article showcases how this brands success signifies a significant stride for the entire Chinese Baijiu industry on the global stage.